The Relationship between Personal Impact of Organizational Change and Employee Commitment: The Mediating Role of Organizational Justice - Imberman, PhD, Maya D; Lopez, Ph.D., Patricia Denise J; Troper, Ph.D., Jonathan D. (ABAC ODI JOURNAL Vision. Action. Outcome, 2017)
Abstract Organizational change famously fails more often than it succeeds and has an impact on employees’ organizational commitment. During times of organizational change, it is important to understand how employee perceptions of the personal impact of change and their assessments of whether the changes are fair will affect their commitment to the organization. The present field study involved a survey of 206 employees from all organizational levels at a division of a Fortune 100 company in the U.S. two and a half years after it underwent restructuring with a significant reduction of force. Results showed that all four dimensions of organizational justice – distributive, procedural, interactional, and informational justice – mediated the influence of personal impact of change (how beneficial or detrimental employees felt the change was for them personally) on affective organizational commitment. In support of fairness heuristic theory, informational justice explained unique variance in affective commitment, above and beyond other justice dimensions. Overall, results showed that management practices perceived as fair will reap the benefits of employee commitment and increase the long-term success of organizational change efforts. Keywords: organizational change, personal impact of change, organizational justice, organizational commitment, organizational restructuring, organizational downsizing, layoff survivors, quantitative